2012
DOI: 10.1055/s-0032-1324729
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of the Treatment of Patients with Disorders of Sex Development

Abstract: Research on the psychological development of persons with Disorders of Sex Development (DSD) has focused on understanding the influence of atypical sex hormone exposure during steroid-sensitive periods of prenatal brain development on the process of psychosexual differentiation (i.e., gender identity, gender role, and sexual orientation). In contrast, analysis of clinical management strategies has focused on gender assignment and the desirability and timing of genital surgery. This review focuses on the psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Patient education in a developmentally sensitive manner is essential to facilitate an optimal medical and psychological follow-up [93]. Although adolescents may be reticent regarding their contact with patient support organizations, the potential benefits of speaking with others who have shared experiences should be reintroduced if initially rejected [16].…”
Section: Information and Decision Making Regarding Male Or Female Assmentioning
confidence: 99%
“…Patient education in a developmentally sensitive manner is essential to facilitate an optimal medical and psychological follow-up [93]. Although adolescents may be reticent regarding their contact with patient support organizations, the potential benefits of speaking with others who have shared experiences should be reintroduced if initially rejected [16].…”
Section: Information and Decision Making Regarding Male Or Female Assmentioning
confidence: 99%
“…. Nurses need to assist patients to overcome the effects of DSD and improve their quality of life (Sandberg, Asciutto, & Haddad, 2011;Sandberg, Gardner, & Cohen-Kettenis, 2012;Zabidi, Zainuddin, & Schmidt, 2016). Nurses may utilize the bio-psycho-social-spiritual model of care to provide holistic care to patients with DSD to help them deal with the physical, psychological, social, and spiritual stressors associated with their condition (Dossey & Keegan, 2015;Rothkopf & John, 2014).…”
Section: Coping Strategiesmentioning
confidence: 99%
“…However, one study reported that 10 out of 217 females, diagnosed with CAH and reared as women, showed some form of gender dissonance or identity confusion. [45] The difficulty in assigning gender particularly arises if the genitalia of the new-born patient is highly virilized. A literature review assessed studies on gender dysphoria and gender confusion in patients with 46 XX CAH reared as females.…”
Section: Introductionmentioning
confidence: 99%